2021
DOI: 10.1097/md.0000000000027594
|View full text |Cite
|
Sign up to set email alerts
|

Observational study of an inpatient program for musculoskeletal disorders

Abstract: A new inpatient secondary preventive program for patients with musculoskeletal health problems was introduced throughout Austria. The aim of the current work was to evaluate this "Health Prevention Active" program and its possible influences on the quality of medical results upon hospital discharge.This observational study presents monocentric data for 7448 patients (48.99 ± 6.15 years; 53.7% women) with chronic musculoskeletal disorders who completed a 3-week health program. The focus was placed on measuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, our sample, consisting predominantly of females with an average age of 67 ± 8 years, is representative of rehabilitation patients with osteoarthritis after knee and hip arthroplasty in Austria [70]. Context and sample characteristics, such as gender or baseline values, play an important role in effect size statistics [69,71], like in sensitivity to treatment evaluation. In contrast, sample characteristics play a minor role in the correlative assessment of external responsiveness when using a criterion-oriented approach [59,72].…”
Section: Discussionmentioning
confidence: 99%
“…However, our sample, consisting predominantly of females with an average age of 67 ± 8 years, is representative of rehabilitation patients with osteoarthritis after knee and hip arthroplasty in Austria [70]. Context and sample characteristics, such as gender or baseline values, play an important role in effect size statistics [69,71], like in sensitivity to treatment evaluation. In contrast, sample characteristics play a minor role in the correlative assessment of external responsiveness when using a criterion-oriented approach [59,72].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to pool the data correctly and to correct for the tendency for different baseline values to occur. Stratified outcome scores for evidence-based determinants of health status are essential for healthcare delivery because the baseline medical condition has the strongest moderating effect on outcome [ 36 ]. The “performance score” (T2D) reflects the fact that patients with a short baseline walking distance have to improve more than individuals with a long baseline walking distance to perform well.…”
Section: Discussionmentioning
confidence: 99%
“…As part of the appraisal for this program, a large observational study was conducted, and the results indicated that physical inactivity is the factor that is most associated with the need for healthcare services. 10 …”
Section: Introductionmentioning
confidence: 99%
“…As part of the appraisal for this program, a large observational study was conducted, and the results indicated that physical inactivity is the factor that is most associated with the need for healthcare services. 10 Using DHC for health improvement is cost-effective, safe, and measurable. 11 In particular, rehabilitation for MSD, which requires physical activity (PA), may have great potential when combined with DHC based on the Internet, smartphone applications, augmented reality (AR), and virtual reality (VR).…”
Section: Introductionmentioning
confidence: 99%